MMC as nonlinear vector current source for grid connection of wave energy generation. (December 2019) - Martinez-Rodrigo, F.; Ramirez, D.; Mendonça, H.; de Pablo, S.
Highlights: Improvement of grid-connected wave power plants and wave energy converters. A new MMC-based strategy for offshore HVDC grid-side converter. Fast control of grid-side HVDC-MMC converters. Abstract: Modular multilevel converter (MMC) is a type of electronic converter currently used as voltage source in real HVDC transmission systems. This paper presents, as an alternative, a control system designed to operate an MMC as a nonlinear vector current source (NLVCS). From the design point of view, it features advantages such as constant switching frequency, robustness against grid parameters changes and that the algorithm is entirely designed from space vectors. From the application point of view, the main advantages are its fast dynamic response combined with its capability to handle large amounts of electric power. Together, these two features allow the MMC to deal with highly variable renewable energies. To show the advantages of the proposed control system, it has been chosen a very demanding application: wave energy. In this type of applications, the random nature of the sea produces large and fast variations of the generated power, that enters the DC link and that the grid side converter has to handle very fast, injecting it into the grid in order to maintain the DC voltage constant. The capability of the NLVCS for MMC to handle the energy generated has been tested in two different wave energy applications. Firstly, on a single wave energy converter (WEC), a point absorber. This case is characterized by smaller and faster power changes. Secondly, on a wave farm made up of 200 WECs connected to the grid through an MMC. This case is characterized by much larger but smoother power changes. Wave farms, WECs and MMC are large and sophisticated facilities or devices that are almost impossible to gather in the same laboratory. Consequently, the features of the new control system for MMC and the advantages that provide in the connection of wave energy power plants and point absorbers to the grid has been simulated using detailed models. The results demonstrated the capability of the MMC operating as NLVCS to deal with the fast and random power changes present in renewable energy sources.